Carbon resource reallocation with emission quota in carbon emission trading system. (1st February 2023) - An, Qingxian; Zhu, Kefan; Xiong, Beibei; Shen, Zhiyang
Abstract: In this study, a two-stage data envelopment analysis approach is developed to examine resource allocation in a real-world carbon emissions trading system. First, this study focuses on the actual participation process of incorporated units in the trading system, where incorporated units will be allocated with a carbon emission quota. Second, we propose a research structure for the carbon trading process with two stages. The first stage is to identify congestion, and the second stage is to trade among the units. We make a sensitivity analysis by considering restrictive parameters on the initial carbon emission quota. Then, we expand the research with a target-setting model that retains production technology from the previous year to set the target output for the following year. The congestion and the trading amount for each unit could be determined in advance. Furthermore, these results are able to anticipate the trading situation and provide valuable recommendations for the production and trading of the analyzed units. Finally, the proposed approach is applied to analyze 13 cities in Hubei Province to investigate their congestion and trading conditions. Highlights: This study fills the gap that most of literature only concerns the effect of ETS. A two-stage structure with considering operational process of ETS is constructed. We focus on the real trading process of each unit in the trading system. We set the production target for each unit in the next year as extension.